Suporte social na adesão ao tratamento antirretroviral para o HIV - Oliveira, Rafael da Silva (2019)
Introduction: The introduction of antiretroviral treatment made it possible to control the epidemic and transformed the human immunodeficiency virus infection into a chronic condition. For effectiveness of the treatment the person must maintain adherence to treatment, which can be positively or negatively impacted by several factors, including social support, a theoretical construct developed in the 1970s. Therefore, this study aims to measure and correlate social support, adherence to treatment and sociodemographic factors that influence both. Method: This is a cross-sectional study, from the matrix project "The use of text messages in adherence to antiretroviral treatment", carried out at the University Hospital of Santa Maria. The sample was composed of 168 participants with the data collection developed from July 2016 to August 2018. This research used a tool for clinical and sociodemographic characterization, a questionnaire for evaluation of ART adherence (CEAT - HIV) and the Social Support Scale for people living with HIV / AIDS. The data collection was made using Epi-info®, version 7.0. After checking for errors and inconsistencies, the data analysis was performed in the SPSS 20.0 for Windows. A descriptive analysis and Spearman's correlation was performed to verify: 1) the relationship between the scores obtained in the antiretroviral treatment adherence scales and other sociodemographic and clinical variables; 2) social support for people living with HIV and other sociodemographic and clinical variables; 3) relationship between social support and adherence. Results: The population of this study consisted of 56% (n = 95) males, whites 64.3% (n = 108), 50.6% (n = 85) are living with their partners. Adherence to treatment was classified as insufficient for 63.7% (n = 107) of the participants. The mean of Social Support score was 3.53 (SD = 0.66). Most participants, 44.6% (n = 75) reported receiving support to follow treatment from close relatives such as parents, mothers, siblings and spouses. Significant positive correlation (p <0.05) between the adherence domains (antecedents of adhesion failure and physician-patient communication) was identified with the emotional social support factor. Conclusions: It is concluded that the participants have social support, mainly coming from the nuclear family and that there are socioeconomic factors that are related to them. Even with emotional and instrumental support considered satisfactory, they were not sufficient to raise the adherence scores, considered insufficient by the classification proposed by CEAT-VIH. We found related emotional support factors with the backgrounds domains of lack of adherence and physician-patient communication.